Anodizing under conditions of oxygen activation of the inter-electrode gap - Kolenchin Nikolay (EDP Sciences, 2021)
Structured alumina is currently used in a wide range of applications. Interest in a surface with a wear-resistant coating motivates creation of methods for high-speed oxidation with an increase in the thickness and hardness of the layer, with obligatory observance of environmental parameters and a decrease in the energy intensity of production. Considering the activity of aluminum towards oxygen, a very important aspect is the search for conditions to increase the natural oxide film to the level of functional significance. The generally accepted scheme of classical anodizing represents a closed system of an electrolytic cell, inside which the elements are activated in the interelectrode gap to the state of ionic excitation under the action of an electric field. The efficiency of interaction depends on the medium’s nature and variability of the volt-ampere parameters. This work proposes a different mechanism for intensifying the process. Oxygen is activated outside the electrolytic cell and in the allotropic state, in the form of ozone, is transmitted into the interelectrode gap. The phase composition, structure, thickness, and microhardness are investigated. The aim of the research is to establish the effect of ozone on the oxidation process.